A novel approach to isolate brain‐cell–derived exosomes from plasma to better understand pathogenesis of Alzheimer's disease: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Kumar, Ashish; Hughes, Timothy M.; Craft, Suzanne; Deep, Gagan
Abstract: Background: Exosomes are nano‐vesicles ∼30‐150 nm in diameter that are released by all cell types and present in all biofluids. Exosomes are loaded with unique cargo, including RNAs, proteins, lipids, and metabolites that relate to the cell of origin and the patho‐physiological state of the organism. Discovery of brain cells‐derived exosomes in the circulation led to studies examining their role as potential mediators as well as 'liquid biopsies' for Alzheimer's disease and related dementias (ADRD). However, currently, most work with exosomes focus on one class of exosome subtype at a time. Here, we have developed a novel and sensitive method to simultaneously extract pure and biologically active exosomes secreted from various cells of the neurovascular unit, including: neuron‐derived exosomes (NDE), astrocytes‐derived exosomes (ADE), endothelial‐derived exosomes (EDE), pericyte‐derived exosomes (PDE), and oligodendrocyte‐derived exosomes (ODE). Method: We employed ExoQuick precipitation method to isolate total exosomes from the plasma of age‐matched individuals with normal cognition or AD. We optimized methods to label specific antibody with photo‐cleavable (PC)‐biotin. Next, we extracted exosomes of the neurovascular unit from the total exosomes using streptavidin coated magnetic beads and biotin or PC‐biotin‐tagged antibodies (L1CAM for NDE; GLAST for ADE; PDGFRα for ODE; CD31 for EDE and PDGFRβ for PDE). To release the exosomes, magnetic beads were exposed to UV light (280 nm). We performed immunogold labelling, transmission electron microscopy (TEM), flow cytometry and ELISA to validate the isolated exosome populations. Result: Following our novel methods, we extracted NDE, ADE, EDE, PDE, and ODE from total plasma exosomes. We validated the purity of each exosome population by flow cytometry, and confirmed the surface expression of exosomal biomarkers (CD63 and CD9) by immunogold labelling and TEM. Lastly, ELISA analyses showed that Aβ1‐42 was absent in all exosome populations from healthy individuals but significant level of Aβ1‐42 was detected in all the exosome populations (NDE, ADE, EDE, PDE, and ODE) from AD patients. Conclusion: We have developed a novel, sensitive and reproducible method to isolate and characterize various brain cells‐derived exosomes from plasma which could lead to development of novel blood based exosomal biomarkers to better understand AD pathogenesis.